2018
DOI: 10.22178/pos.33-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ticks on Camels and Cattle Brought to Dodoru Market Kebbi State, Nigeria

Abstract: Dodoru Market is popular for its weekly Market day in Kebbi State, Nigeria. People converge at the market every Monday from various places to buy or sell. Survey of ticks on camels and cattle brought to Dodoru Market for sale was conducted. The aim was to evaluate the prevalence of camel and cattle ticks. A total of 90 animals (40 camels and 50 cattle) were examined. Five tick species were identified and prevalence was evaluated. Results revealed that 32 of the camels were infected with the prevalence of 35.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
7
2
Order By: Relevance
“…Hyalomma dromedarii was the most frequent tick species encountered in this study. Similar observations have also been reported by other researchers on ticks of camels in Nigeria [ 47 , 49 , 50 ], within other African countries [ 55 , 56 ] and other parts of the world [ 57 , 58 ]. The dromedary camel was found to be the preferred host for this tick species, but it also infests sheep, goats, cattle and horses [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Hyalomma dromedarii was the most frequent tick species encountered in this study. Similar observations have also been reported by other researchers on ticks of camels in Nigeria [ 47 , 49 , 50 ], within other African countries [ 55 , 56 ] and other parts of the world [ 57 , 58 ]. The dromedary camel was found to be the preferred host for this tick species, but it also infests sheep, goats, cattle and horses [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study confirmed the occurrence of several tickborne pathogens and the species diversity of ticks infesting camels in Nigeria. The overall rate of tick infestation in this study was 52.3%, lower than 80.0% reported by Abdullahi et al [47] in Kebbi state, Nigeria. Differences between the two studies could be basically attributed to the smaller sample size in the latter study.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Maiduguri and Yobe State) [10][11], or western States (e.g. Sokoto and Kebbi States) [19][20][21][22], limiting in some instances the identification of ticks to the genus level [10,11,20]. Similarly, the majority of studies on TBPs in Nigeria, detecting the presence of apicomplexan parasites belonging to the genera Theileria and Babesia, and members of the bacterial genera Anaplasma, Ehrlichia, Rickettsia and Coxiella spp., have mostly relied on cytological (i.e.…”
Section: Introductionmentioning
confidence: 99%